The Future of Radiobiology. (3rd November 2017) - Kirsch, David G; Diehn, Max; Kesarwala, Aparna H; Maity, Amit; Morgan, Meredith A; Schwarz, Julie K; Bristow, Robert; Demaria, Sandra; Eke, Iris; Griffin, Robert J; Haas-Kogan, Daphne; Higgins, Geoff S; et al.
Abstract: Innovation and progress in radiation oncology depend on discovery and insights realized through research in radiation biology. Radiobiology research has led to fundamental scientific insights, from the discovery of stem/progenitor cells to the definition of signal transduction pathways activated by ionizing radiation that are now recognized as integral to the DNA damage response (DDR). Radiobiological discoveries are guiding clinical trials that test radiation therapy combined with inhibitors of the DDR kinases DNA-dependent protein kinase (DNA-PK), ataxia telangiectasia mutated (ATM), ataxia telangiectasia related (ATR), and immune or cell cycle checkpoint inhibitors. To maintain scientific and clinical relevance, the field of radiation biology must overcome challenges in research workforce, training, and funding. The National Cancer Institute convened a workshop to discuss the role of radiobiology research and radiation biologists in the future scientific enterprise. Here, we review the discussions of current radiation oncology research approaches and areas of scientific focus considered important for rapid progress in radiation sciences and the continued contribution of radiobiology to radiation oncology and the broader biomedical research community.